2 Corinthians 5:1-10: Watershed in Paul’s Eschatology - Harris, M. J. (Tyndale bulletin, 1971)
A paper highlighting three issues arising from 2 Corinthians 5:1-10 which impinge directly on the notion of development in Paul's eschatological thought.